PD‐L1 and thyroid cytology: A possible diagnostic and prognostic marker. Issue 3 (10th December 2019) - Dell'Aquila, Marco; Granitto, Alessia; Martini, Maurizio; Capodimonti, Sara; Cocomazzi, Alessandra; Musarra, Teresa; Fiorentino, Vincenzo; Pontecorvi, Alfredo; Lombardi, Celestino Pio; Fadda, Guido; Pantanowitz, Liron; Larocca, Luigi Maria; et al.
Abstract : Background: Programmed death‐ligand 1 (PD‐L1) expression is emerging as an important predictive biomarker in anti–PD‐L1 cancer immunotherapy. Its role has been clearly defined in various human cancers and is linked to a poor prognosis and resistance to anticancer therapies. The role of PD‐L1 in thyroid cancers has not been well defined in fine‐needle aspiration cytology (FNAC). The authors examined the performance of PD‐L1 immunostaining in liquid‐based cytology (LBC) to determine whether it could be a biomarker of malignancy or aggressive disease. Methods: From January 2018 to March 2019, 236 thyroid lesions, which had been diagnosed by FNAC as indeterminate lesions, suspicious for malignancy (SFM), and malignant, were enrolled. PD‐L1 immunostaining was performed on both LBC and corresponding histology samples. Results: The FNAC cohort included 50 benign negative controls, 42 samples of atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS), 33 samples of follicular neoplasm/suspicious for follicular neoplasm (FN/SFN), 53 samples that were suspicious for malignancy (SFM), and 58 malignant samples. AUS/FLUS samples included 3 goiters, 32 follicular adenomas (FAs), 1 noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP), 5 invasive follicular variants of papillary thyroid carcinoma (I‐FVPTCs), and 1 follicular carcinoma; whereas FN/SFN samples included 24 FAs and 9 malignancies (4 I‐FVPTCs, 1 NIFTP, 3 papillary thyroid carcinomas [PTCs], and 1 oncocytic follicular carcinoma). The 53 SFM samples were diagnosed on histopathology as 2 FAs, 5 NIFTPs, 15 I‐FVPTCs, and 31 PTCs; whereas the 58 malignant specimens included 5 NIFTPs, 5 I‐FVPTCs, and 48 PTCs. Increased plasma membrane and cytoplasmic PD‐L1 expression was found in 79 cases (38.5%), including 61 PTCs (conventional and variants). Negative PD‐L1 expression was found in NIFTPs and FAs. A BRAF V600E mutation was identified in 15% of PD‐L1–positive malignancies. Conclusions: The current data suggest that PD‐L1 expression in the thyroid gland might represent a marker of malignancy that correlates with PTC, but not with NIFTP. Thyroid neoplasms with PD‐L1 expression also ae enriched with BRAF V600E mutations, suggesting that they are associated with more aggressive behavior. Abstract : Programmed death‐ligand 1 (PD‐L1) expression correlates with papillary thyroid carcinoma and its variant but only partially correlates with BRAF V600E mutations. The lack of PD‐L1 expression seems to support the concept that noninvasive follicular thyroid neoplasm with papillary‐like nuclear features is a nonmalignant neoplasm.